To solve the equation \( 37x + 67 - 2x = 4 \), we can follow these steps:
-
Combine like terms on the left side: \[ 37x - 2x + 67 = 4 \] This simplifies to: \[ 35x + 67 = 4 \]
-
Subtract 67 from both sides: \[ 35x + 67 - 67 = 4 - 67 \] This simplifies to: \[ 35x = -63 \]
-
Now, divide both sides by 35: \[ x = \frac{-63}{35} \] Simplifying \(\frac{-63}{35}\) gives: \[ x = \frac{-63 \div 7}{35 \div 7} = \frac{-9}{5} \]
-
\(\frac{-9}{5}\) is not one of the options you've provided. Let’s check if the options make up a mistake:
You listed four potential answers: \(2, 22, -22, -2\).
Since the calculated answer does not match any of the given options, could it be possible that the options were listed incorrectly?
If you were to reconsider the equation or approach, please provide any corrections or further instructions. Otherwise, based upon the calculation above, the solution would be correct in its form.